Rekonstruksi Teori Penemuan Hukum di Era Digital Terkait Peran AI dalam Proses Peradilan (Studi Perbandingan Indonesia dan Tiongok) - Nur Rizkiah Hasanah; Irena Puspa Mega; Ivan Nurchalik (Journal of Innovative and Creativity, 2025)
The advancement of digital technology in the era of the Fourth Industrial Revolution has driven significant transformation across various sectors, including the field of law and judiciary. One of the key innovations emerging from this shift is the use of Artificial Intelligence (AI) to enhance efficiency and expedite case processing. This study aims to examine the implementation of AI in the Chinese judicial system, particularly through the innovation of the AI Prosecutor robot known as "The AI", and to evaluate its potential application within the Indonesian judicial context. Additionally, the study revisits the theory of legal discovery (rechtsvinding) within Indonesia’s legal system to align it with technological developments without compromising the principles of substantive justice and judicial independence. This research employs a normative juridical method with a comparative law approach, supported by literature review of primary and secondary legal sources. The findings indicate that although AI can support judicial processes through rapid and systematic legal data analysis, its use must remain limited to an assistive role under strict human supervision. AI cannot replace the role of judges in the legal discovery process, which inherently involves ethical considerations, human experience, and moral reasoning. Therefore, a firm and ethical legal framework is needed to regulate the use of AI in the judiciary, alongside the development of a hybrid model that positions AI as a supportive tool rather than a primary decision-maker.